Public willingness to commit time to urban forestry development in Lagos metropolis, Nigeria (2015)
This study assessed willingness of Lagos metropolitans to commit time and the prospective number of hours to be committed to Urban Forestry Development (UFD) in the metropolis. Data were obtained from a questionnaire survey of 900 metropolitans living in three income profiled neighbourhoods using the payment card contingent valuation method. Data were analysed with descriptive statistics and Tobit model at p= 0.10. Results show that 48% of the respondents were willing to commit their time to UFD in the metropolis, out of which 13.9% were willing to commit a modal two hours per week (h/w) to the UFD. Moreover, 53.1%, 50.8%, 71.1%, 47.6%, 65.4% respectively of those who love to live or work in green environment, were aware of benefits of trees in urban environment They either belonged to social organizations, owned their residences, or previously participated in community projects and were willing to commit time to the UFD. Twelve of the 32 regressors (constant inclusive) had significant influence on the probability to commit time and the number of hours to commit per week to urban forestry development in Lagos metropolis. To harness the great pool of volunteers for urban forestry development in Lagos metropolis, promoters and protagonists of urban greening in the metropolis will have to put in place an appropriate formal public education programme to enlighten the metropolitans on the benefits of trees in urban environment; bring together social organizations, CBOs, NGOs etc. for the use o f educating and eliciting support of the public for UFD among others.